2021
DOI: 10.1111/odi.13766
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CD168 is related to poor prognosis in oral squamous cell carcinoma

Abstract: Objectives: Receptor for hyaluronic acid (HA)-mediated motility (RHAMM) is also known as CD168. This study proposed to elucidate the prognostic and clinicopathological significance of CD168 expression in oral squamous cell carcinoma (OSCC). Materials and methods:Immune staining of a human tissue microarray and Western blot were used to reveal the expression level of CD168 in OSCC. Correlations between clinicopathological indexes and CD168 expression in OSCC patients were assessed.Results: Increased expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…RHAMM expression was not an independent prognostic factor although previous studies have shown increased RHAMM expression in PC (18,19). Most RHAMM expression analyses revealed that elevated RHAMM expression was associated with worse prognostic factor in many cancers, including breast cancer (29), oral squamous cell carcinoma (30), ovarian cancer (31), lung cancer (15), colon cancer ( 16), gastric cancer (14), and pancreatic cancer (13). Our study demonstrated that RHAMM overexpression enhances the malignant potential of PC.…”
Section: Discussionmentioning
confidence: 44%
“…RHAMM expression was not an independent prognostic factor although previous studies have shown increased RHAMM expression in PC (18,19). Most RHAMM expression analyses revealed that elevated RHAMM expression was associated with worse prognostic factor in many cancers, including breast cancer (29), oral squamous cell carcinoma (30), ovarian cancer (31), lung cancer (15), colon cancer ( 16), gastric cancer (14), and pancreatic cancer (13). Our study demonstrated that RHAMM overexpression enhances the malignant potential of PC.…”
Section: Discussionmentioning
confidence: 44%
“…Accumulating investigations have uncovered the important biological functions of circRNAs in the development of various cancers, 4 including OSCC. 20 For example, multiple circRNAs, such as circFNDC3B, circEPSTI1, and circ_LPAR3, have been identified as strong promoters in OSCC progression and metastasis. [21][22][23] Moreover, circ_0069313 contributes to OSCC immunity escape to induce this disease progression by targeting miR-325-3p/Foxp3 axis.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the selective delivery of HA-CA4P-NP to OSCC cells. Low fluorescence was generated after incubation of HA-CA4P-NP with non-cancer HNEC, further indicating that HA-based NPs actively target cancer cells, probably because RHAMM receptors are highly expressed in cancer cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%